Immunization Status of Children Admitted to a Tertiary-care Hospital of North India: Reasons for Partial Immunization or Non-immunization (Journal of Health, Population and Nutrition, 2010)
Reasons for the low coverage of immunization vary from logistic ones to those dependent on humanbehaviour. The study was planned to find out: (a) the immunization status of children admitted to apaediatric ward of tertiary-care hospital in Delhi, India and (b) reasons for partial immunization and nonimmunization.Parents of 325 consecutively-admitted children aged 12-60 months were interviewed usinga semi-structured questionnaire. A child who had missed any of the vaccines given under the nationalimmunization programme till one year of age was classified as partially-immunized while those who hadnot received any vaccine up to 12 months of age or received only pulse polio vaccine were classified asnon-immunized. Reasons for partial/non-immunization were recorded using open-ended questions. Ofthe 325 children (148 males, 177 females), 58 (17.84%) were completely immunized, 156 (48%) werepartially immunized, and 111 (34.15%) were non-immunized. Mothers were the primary respondents in84% of the cases. The immunization card was available with 31.3% of the patients. All 214 partially- orcompletely-immunized children received BCG, 207 received OPV/DPT1, 182 received OPV/DPT2, 180received OPV/DPT3, and 115 received measles vaccines. Most (96%) received pulse polio immunization,including 98 of the 111 non-immunized children. The immunization status varied significantly (p